Agricultural Extension in Post-COVID Era: Lessons Learned and Path Forward - Jyoti Zirmire; Debikarani Chungkham; Prathamesh Dilip Jagtap; Gariyashi Tamuly; Narinder Panotra; Saurabh; Prasanta Protim Hazarika (Archives of Current Research International, 2025)
This review examines the impact of the pandemic on agricultural extension systems, focusing on adaptive strategies, lessons learned, and innovations shaping the path forward. The COVID-19 pandemic posed unprecedented challenges to agricultural extension services worldwide, especially in developing regions. Food and agriculture issues are subsequently emerging in several countries at an unprecedented scale. At the same time, the negative implications of the pandemic on food security and livelihoods in the country point to the need for scaling up of efforts to mitigate the impacts of the crisis. Lockdowns, market disruptions, and mobility restrictions significantly hindered traditional face-to-face extension practices, compelling a rapid shift toward digital and remote modalities. In response, stakeholders adopted alternative methods, including virtual training, mobile applications, and community engagement tools, to sustain support for farmers. The pandemic exposed systemic weaknesses such as resource constraints, technology gaps, communication barriers, and limited inclusivity in extension delivery. However, it also accelerated the adoption of ICT-driven approaches and fostered collaborative networks among public, private, and non-governmental actors. Emphasis on resilience, sustainability, and climate-smart practices emerged as key pillars in reimagining extension services post-COVID. The review underscores the critical importance of investment in technology, capacity-building, stakeholder collaboration, and policy reforms to enhance the effectiveness and adaptability of extension systems. Drawing insights from global and local case studies, the paper advocates for a more inclusive, digitally integrated, and responsive agricultural extension model that can withstand future shocks. Ultimately, the COVID-19 crisis, while disruptive, catalyzed innovation, urging a transformation in agricultural extension to ensure food security and sustainable livelihoods.